Personality Types of Underachiever Students and the Implication for Guidance and Counseling Services - Novi 'Aturrahmi; Zikra Zikra (Jurnal Neo Konseling, 2019)
Underachiever is a student who achieves below the level of ability or students who are expected to achieve an achievement with the level of ability possessed, but the reality is not as expected. Students who have a high level of ability can actually achieve an achievement. However, the reality in the field was found by students who had high intelligence but had low achievement in school. The purpose of this study is to describe the personality types of underachiver students in terms of personality types coasting underachiever ,  anxious underachiever , defiant underachiever,  wheeler-dealer underachiever, identity search underachiever, sad or depressed underachiever and their implications for guidance and counseling. This type of research is quantitative research with a descriptive approach. The research was conducted in SMA N 3 Bukittinggi by involving 50 students underachiever class X and XI as a research subject. Data obtained by giving an instrument in the form of questionnaires to underachiever students . Then the data obtained is analyzed using percentage techniques.The findings of the study are the type of personality coasting underachiever are very hight category, type of personality anxious underachiever in the quite high category, personality types defiant underachiever in the very low category, the type personality wheeler-dealer underachiever in the low category, the type of personality identity search underachiever in the category of very low, the type of personality sad or depressed underachiever that are in the low category.